MASALAH-MASALAH PARTAI POLITIK INDONESIA - Sri Lestari Wahyuningroem (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2021)
This research departed from the low score of political parties in Indonesian Democracy Index. Assuch, this paper tries to analyze as to the primary problems faced by political parties in the era of reformation with previously giving historical backgrounds regarding to political parties’ transformation in Indonesia. The main purpose of this research is to identify obstacles and opportunities so as to strengthening political parties towards consolidated democracy. The study finds that there are three main issues faced by political parties in reform era, which are corruption, money politics, and the failure of political representation. other problems are about accountability, transparency, and political party funding, in which the income and the outlay of political parties are not balanced so that triggering the possibility of corruption. Subsequently, there are some challenges which later known in the effort of strengthening political parties, which are patronage, clientelism, and supervising policy by government.